Optimasi Tingkat Kepuasan Mahasiswa Universitas Budi Luhur Melalui Pendekatan Analisis Faktor - Hendrawan, Koen; Widyastuti, Umi; Sariwulan, Tuti; Yohana, Corry (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aim to evaluate of student satisfaction at Budi Luhur University. This approach involves identifying the factors that determine satisfaction and determining the factors that are most dominant in the quality of UBL Teaching and Learning, as well as looking for indicators that make up these dominant factors. Data for this research was obtained through distributing questionnaires to students from 4 faculties, with a total sample of 302 students. Data analysis was carried out using two main methods, namely Descriptive Analysis and Factor Analysis. The purpose of Descriptive Analysis is to provide a general description of the factors that influence student satisfaction with Budi Luhur University student learning activities. Meanwhile, Factor Analysis is used to identify the main factors that student satisfaction. The research results show that overall, students have a sufficient level of satisfaction with teaching and learning activities at Budi Luhur University. The most dominant factor in determining student satisfaction is tangible. Therefore, increasing student satisfaction can be increased by increasing other factors which level of mastery is still low. The implications of these findings can be used as a basis for developing strategies and improving student teaching and learning activities, to improve the student experience at Budi Luhur University.